Enhanced recovery for thoracic surgery in the elderly. Issue 1 (February 2018) - Shepherd, Stephen J.; Klein, Andrew A.; Martinez, Guillermo
Abstract : Purpose of review: Both surgical workload and the age of those patients being considered for radial pulmonary resection are increasing. Enhanced recovery programmes are now well established in most surgical disciplines and are increasingly reported in thoracic procedures. This review will discuss the relevant principles of these programmes as applied to an increasing elderly population. Recent findings: Elderly patients undergoing less radial surgical resections without lymphadenectomy have comparable outcomes to those undergoing classical curative treatment. Patients require careful assessment and self-reported quality of life metrics or function may be a better marker of outcome than static measures such as lung function. Hypotension, low values for bispectral index and low anaesthetic gas mean alveolar concentration values are common and independent predictors of mortality in the elderly. Paravertebral blockade is preferred to epidural anaesthesia because of a more favourable side-effect profile and comparable efficacy. As yet no robust work has examined the efficacy of an integrated enhanced recovery programme in thoracic surgery. Summary: Elderly patients are suitable for enhanced recovery programmes but these must be tailored to individual circumstance. Further work is required to comprehensively assess their value in a modern healthcare setting.